A checklist of the bryophytes of Andorra. (2nd October 2017) - Sotiaux, Andre; Vanderpoorten, Alain
Abstract : A checklist of 137 liverwort and 445 moss species is established for Andorra based on a review of the literature and a long-term floristic survey. Five moss species, Barbula amplexifolia, Ditrichum zonatum, Grimmia donniana, Pohlia bulbifera, and P. lutescens, are new to the Iberian Peninsula. Another 7 liverwort and 156 moss species are new to Andorra. For each species, the distribution at the scale of 1 km 2 and altitudinal range are documented, resulting in an improved assessment of the frequency and distribution of 101 moss species previously reported from a single record. Haplomitrium hookeri and Scapania verrucosa, which are the two Regionally Extinct species of the Spanish Red List of liverworts, occur in Andorra, which hosts between 23 and 37% of the species listed as Critically Rare, Endangered, or Vulnerable in the Spanish Red List of bryophytes. Therefore, it appears that Andorra is a key area for the conservation of the high-altitude flora of the Iberian Peninsula.